Hygiene and Health in Developing Countries Recent Advances - Šostar Turk, Sonja; Rozman, Urška (IntechOpen, 2022)
Safe drinking water, sanitation, and hygiene are crucial to human health and wellbeing. These factors are a prerequisite to health since they play a crucial role in preventing the transmission of numerous waterborne pathogens and chemical contaminants. Another important factor that can affect people's health is air pollution. Special attention needs to be paid to developing countries, as these factors not only affect human health but also contribute to livelihoods, school attendance, and dignity and help create resilient communities living in healthy environments. This book provides insights into different aspects of hygiene, sanitation, water, and air pollution and their potential correlation with infectious diseases and human health. It also addresses important challenges and opportunities for improvement in developing countries. These are priority areas in which the world's leading health and humanitarian organizations, such as the WHO and UNICEF, are working intensively.